A comparative study of the incidence of malocclusion among the homogenous and admixed kankana-ey population - Asprah, Ma. Xerezida F.; Bautista, Jennifer A.
Tests have documented the inadequacy of single gloving in preventing cross - infection. Double gloving has been suggested to be a more efficient physical barrier. This study aimed to evaluate the presence of macroporosities and microporosities on both unused and used single and double gloving techniques. Tests were conducted on a total of 140 gloves (unused and used single and double gloving techniques) on permeability to ions, propylene -glycol red dye and air to a 0.05 level of significance. Scanning Electron Microscope showed mean porosity size for single gloves at 12.83 microns and 2.58 microns for double gloves, therefore holes in single gloves were found to be 203.43% to 436.93% larger than holes in double gloves to a 0.00 level of significance. Electroconductivity, dye leakage and air bubble tests showed double gloving to be significantly more efficient as a physical barrier to single gloving using ANOVA, F - Test, Duncan's Test and Tukey's HS Difference Test.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Malocclusion